Pemanfaatan Piezoelektrik pada Tanggul Pengaman Jalan (Polisi Tidur) sebagai Sumber Energi Listrik Lampu Penerangan Jalan - Ayu Fitriah Sapruddin; Alda Dwiyanti; Justin Gilbert Kude Songe (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
The increasing number of motor vehicles in Indonesia produces repetitive mechanical loads on road surfaces that are rarely converted into useful energy. This study designs and evaluates a piezoelectric energy-harvesting speed bump intended to support low-power street lighting. The prototype integrates 25 piezoelectric discs (50 mm diameter) connected in series, an AC–DC bridge rectifier, a 2.7 V/500 F supercapacitor for short-term storage, and a DC–DC step-up converter to charge a 12 V battery. Field tests used a motorcycle at speeds of 5, 10, and 15 km/h with rider masses of 48, 70, and 79 kg; each condition was repeated ten times and averaged. Output voltage, current, and electrical energy per pass were measured after rectification. Results indicate that higher speed and mass increase electrical output, with a peak energy of 0.021 J at 15 km/h and 70 kg and an estimated conversion efficiency of about 0.20%. After repeated charging cycles, stored energy powered a 12 V/20 W LED lamp for several minutes. The proposed integration of series piezoelectric elements with supercapacitor buffering and step-up regulation demonstrates a feasible micro-energy harvester for traffic-dense areas and provides a basis for durability and scaling studies. Future work addresses packaging, fatigue, and multi-vehicle loading.